Additive manufacturing of magnetocaloric (La, Ce)(Fe, Mn, Si)13–H particles via polymer-based composite filaments. (November 2022) - Díaz-García, Á.; Revuelta, J.; Moreno-Ramírez, L.M.; Law, J.Y.; Mayer, C.; Franco, V.
Abstract: Additive manufacturing could be an excellent way of shaping magnetocaloric heat exchangers in magnetic refrigerators. However, the metal additive manufacturing techniques present the serious limitation that the melting of a magnetocaloric material can cause its transformation and the loss of functionality. Fused deposition modeling using polymer-based composite filaments is presented as a promising alternative as temperatures are low enough to preserve the magnetocaloric material. To prove this claim, a polymer-based composite filament containing 55 wt% of (La, Ce)(Fe, Mn, Si)13 –H magnetocaloric fillers has been manufactured using custom-made polymer capsules as the feedstock for the extrusion. Both adiabatic temperature change and isothermal entropy change have been characterized for the fillers, as-prepared filaments and as-printed parts, indicating that the magnetocaloric material functionality is not altered along the whole process. Printing resolution is comparable to the raw PLA filament. Highlights: Composite filament of PLA and La(Fe, Si)13 –H particles fabricated with uniform concentration. Fraction of the active phase and hydrogenation remain unaltered after fabrication. Reduction of extrusion temperature below dehydrogenation temperature is key. Printability of the filament is demonstrated without changes in MCE properties. Lock-in thermography is used for determining Δ T r e v of printed sample.